2014
DOI: 10.1155/2014/536510
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Preconditioning Elevates p-Akt and Cardiac Contractility after Reperfusion in the Isolated Ischemic Rat Heart

Abstract: Insulin induces cardioprotection partly via an antiapoptotic effect. However, the optimal timing of insulin administration for the best quality cardioprotection remains unclear. We tested the hypothesis that insulin administered prior to ischemia provides better cardioprotection than insulin administration after ischemia. Isolated rat hearts were prepared using Langendorff method and divided into three groups. The Pre-Ins group (Pre-Ins) received 0.5 U/L insulin prior to 15 min no-flow ischemia for 20 min foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 29 publications
3
21
1
Order By: Relevance
“…[14, 15] Cardiomyocytes perfused with insulin had elevated p-Akt levels prior to ischemia compared with those that did not receive insulin [3]. Similarly, in the present study, insulin pre-conditioning was associated with increased myocardial p-Akt concentrations.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…[14, 15] Cardiomyocytes perfused with insulin had elevated p-Akt levels prior to ischemia compared with those that did not receive insulin [3]. Similarly, in the present study, insulin pre-conditioning was associated with increased myocardial p-Akt concentrations.…”
Section: Discussionsupporting
confidence: 71%
“…Pharmacological options include the pre-emptive administration of volatile anesthetics, adenosine, nicorandil, delta opioids and nitroglycerin [2]. Recently, insulin also demonstrated cardioprotective qualities when given prior to an ischemic insult [3, 9]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of evidence indicates that insulin increases the tolerance to ischemia/reperfusion [44][45][46]. Different experimental [47,48] and clinical studies [49][50][51] observed a beneficial effect of glucoseinsulin-potassium (GIK) infusion against myocardial reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%